Sustainable development in northern urban areas - Sweet, Pamela (Canadian Institute of Planners, 2004)
Sustainable development principles are an important starting point for the planning of any urban area. In northern communities, where these principles are particularly critical, they are a challenge to implement. Sustainability has a different meaning in the Arctic. This article explores sustainable development principles with examples of implementation from Iqaluit. La planification d'un espace urbain, quel qu'il soit, ne saurait ignorer d'emblée les principes du développement durable. Dans les collectivités nordiques, ces principes sont particulièrement saillants, mais leur mise en oeuvre est épineuse. En effet, le développement durable est autrement compris dons l'Arctique. Cet article aborde les principes du développement durable dans la perspective d'exemples de leur mise en oeuvre à Iqaluit. https://viurrspace.ca/bitstream/handle/10613/5902/Article008.pdf?sequence=3 Abstract in English and French; text in English.